Higher Education in Ireland : Practices, Policies and Possibilities - Loxley, Andrew; Seery, Aidan; Walsh, John; SpringerLink (Online service) (London : Palgrave Macmillan UK, 2014)
This collection provides the first in-depth, interdisciplinary and over-arching review of higher education in Ireland, situating higher education within the socio-cultural, political and historical context of the country over the past 40 years and the development of European and national policies.
Keywords: Social sciences; Great Britain -- History; School management and organization; School administration; Educational sociology; Higher education; Education and sociology; Sociology, Educational; Education and state; Social Sciences; Sociology of Education; Education Policy; History of Britain and Ireland; Higher Education; Administration, Organization and Leadership